Effects of Concomitant Use of N-acetylcysteine and Cyclosporine A on Acetaminophen-induced Acute Kidney Injury in Mice - Kocamueftueoglu, Gonca Ozan; Tektemur, Nalan Kaya; Guzel, Elif Erdem; Tektemur, Ahmet; Ozan, Ibrahim Enver (Agricultural Research Communication Centre, 2024)
Background: Acetaminophen (APAP), a commonly used analgesic, causes acute kidney injury (AKI) in overdose although it is rare. Mitochondrial dysfunction plays a major role in the pathophysiology of renal damage, although the exact molecular mechanism is unknown. This study aimed to evaluate the potential therapeutic effect of cyclosporin A (CsA), a mitochondrial membrane permeability Methods: Male BALB/c mice were divided into Control, APAP, APAP+NAC, APAP+CsA and APAP+NAC+CsA groups (n=6). A single dose of APAP (400 mg/kg) was administered intraperitoneally. All other treatments (1200 mg/kg NAC, 50 mg/kg CsA) were performed intraperitoneally 3 h after APAP administration. All animals were decapitated and blood samples and kidney tissue samples were collected for evaluation. Serum creatinine (Cr) and blood urea nitrogen (BUN) levels were measured. The kidney tissue 8-hydroxydeoxyguanosine (8-OHdG), cytochrome c (Cytc) and 3-nitrotyrosine (3-NT) levels and cytochrome c (Cytc) expressions were determined. Result: Increased Cr and BUN levels, histopathological examinations and expressions of 8-OHdG, 3-NT and Cytc were detected in the APAP group. Combined NAC+CsA treatment sufficiently reversed oxidative stress, serum Cr and BUN levels and histopathological alterations induced by APAP. Moreover, cytc levels and renal tubular injury were remarkably reduced by combined drug treatment compared to the APAP+NAC group. These data suggest that the therapeutic effect of combined NAC+CsA treatment in mice with APAP-induced nephrotoxicity can be related to the combination of the antioxidant effect of NAC and the mitochondrial MPTP inhibitor effect of CsA.
Keywords: 3-nitrotyrosine; 8-Hydroxy-deoxyguanosine; Combined drug treatment; Cytochrome c; Mitochondrial dysfunction; Nephrotoxicity